Filsafat Ilmu sebagai Dasar dan Arah Pengembangan Sistem Hukum di Indonesia - Lindra Darnela (UIN Sunan Kalijaga Yogyakarta, 2012)
Philosophy of science that seem very theoretical, it is necessary to be able to greatly contribute to the practical needs of the community in building a better legal and in accordance with the ideals of law society toward justice. Philosophy of science could be